The Effect of Aloe vera and Glycerol Addition on Edible Film of Lesser Yam Starch (Dioscorea esculenta L. Burkill) - Devi Dwi Siskawardani; Warkoyo Warkoyo; Anggit Ayu Pradana Siwi (Universitas Muhammadiyah Malang, 2020)
Edible films are thin layers made from hydrocolloids, lipids, and their combinations, functioning as a barrier to mass transfer. The hydrocolloid source that commonly used for edible film is starch. Lesser yam has the potential to be developed into food packaging products. It has a high starch yield (21.4%). The starch properties, which usually obstruct the edible film production are not resistant to high temperature, it produces a starch suspension with viscosity and ability to form a gel is not uniform, cannot stand in acidic conditions, does not resist stirring, limited solubility in water, and starch gel is easy to syneresis and brittle. This study aimed to investigate the effect of glycerol and Aloe veraconcentrations on the physical and mechanical edible film. Randomized complete block design (RCBD) factorial with two factors was adopted. The first factor was Aloe vera concentration (0, 1%, 0.2% and 0.3% w/v), and the second factor wasglycerol concentration (17.5, 22.5 and 27.5% v/w). The parameters tested included thickness, tensile strength, elongation, solubility, transparency, and water vapor transmission rate (WVTR). The results showed an interaction between the addition of glycerol and Aloe vera to thickness, tensile strength, elongation, solubility, transparency, and WVTR. The best characteristics of edible film were produced by the addition of glycerol 17.5% and Aloe vera 0.1% with thickness (0.08 mm), transparency (1.72 mm-1), tensile strength (0.156 MPa), elongation (17.25%), solubility (53.89%), and WVTR (4.09 g m-2 24 h-1).